Modeling the Deformation Regime of Thwaites Glacier, West Antarctica, Using a Simple Flow Relation for Ice Anisotropy (ESTAR). Issue 3 (5th March 2022) - McCormack, F. S.; Warner, R. C.; Seroussi, H.; Dow, C. F.; Roberts, J. L.; Treverrow, A.
Abstract: Ice deformation dominates the evolution of ice shelf flow and the slow‐moving regions in the interior of ice sheets. However, deformation may be poorly represented in large‐scale ice sheet models that use the Glen flow relation, due to its questionable applicability to the steady‐state flow of anisotropic ice that prevails in ice sheets, having been derived from secondary creep rates of isotropic ice. We assess the deformation regimes of Thwaites Glacier, West Antarctica, using the Glen and "Empirical Scalar Tertiary Anisotropy Regime", (ESTAR) flow relations, the latter being derived from steady‐state deformation rates of anisotropic ice. For grounded ice, the character of the flow relation determines the contribution of deformation to overall flow, with ESTAR producing greater bed‐parallel shear deformation than the standard Glen flow relation. The ESTAR experiments show larger basal shear stress maxima than the standard Glen experiment because ESTAR treats the responses to simple shear stresses and compression stresses differently, reducing the role of lateral and longitudinal stresses in momentum balance. On the Thwaites Glacier Tongue, ESTAR provides the best match to observed speeds by accounting for the differing effects of stresses on ice flow. Our results highlight the importance of the numerical description of anisotropy, particularly: In regions of transition from deformation‐dominated to sliding‐dominated flow; in the approach to the grounding line, and across ice shelves. Given the importance of these locations in determining mass flux into the ocean, our results have implications for projections of sea level change from Antarctic ice loss. Plain Language Summary: Glacial ice flows by stress‐driven deformation, involving movement within and between ice crystals, and also by sliding at the bedrock in the presence of meltwater. The rate of deformation in large‐scale models of polar ice sheets is usually described by the Glen flow relation, which is limited in how appropriately it describes deformation in the long‐term, nearly steady flows typical of ice sheets. We compare modeling of the deformation regimes of Thwaites Glacier, West Antarctica, using the Glen and Empirical Scalar Tertiary Anisotropy Regime (ESTAR) flow relations. ESTAR was formulated to represent more realistically the deformation rates that occur under prolonged stress, where the orientations of individual ice crystals develop into significantly organized patterns. ESTAR predicts more vertical shear deformation than the Glen relation, leading to faster flow over most of the Thwaites catchment, and particularly in slow‐moving regions in the interior where modeling with the Glen relation predicts unrealistic sliding. ESTAR also provides a better match to the observed surface speeds on the floating Thwaites Glacier Tongue. Our results highlight how improved descriptions of deformation change the distribution of stresses and the relative contributions of deformation and sliding to overall ice flow. Key Points: Flow relations that account for tertiary creep and anisotropy change the simulated contributions of deformation and sliding to overall flow Ice in tertiary creep is softer leading to increased simulated vertical shear deformation where bed parallel shear stresses dominate How flow relations account for anisotropy influences the simulated contributions of longitudinal and transverse stresses in momentum balance